(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
This article provides an analysis of the work carried out in the order of the claim, in particular the concept and elements of the claim, the means of combining and separating the claims of the claim, the means of protecting the interests of the defendant, the basis and procedure for securing the claim, as well as feedback, materials of practice. In addition, the similarities and differences and the specifics of the claim issues were discussed in the civil proceedings of the Central Asian States.